Charting the scorched trails: a comparative analysis of roadway damage from historical megafires to the unprecedented 2020 Labor Day wildfires on the USA West Coast - Kevin Christiansen; Ayat Al Assi; Rubayet Bin Mostafiz; Robert V. Rohli (Emergency Management Science and Technology)
Roadways in the US states of Washington (WA), Oregon (OR), and California (CA) incurred extraordinary damage during the 2020 Labor Day wildfires. However, the cost and risk of these fires have not been placed in a historical perspective. This study examines the damage to roadways affected by the 2020 Labor Day wildfires in relation to the history of megafires in WA (1902–2023), OR (1845–2023), and CA (1889–2023) using carefully selected data sets gathered from the Washington State Department of Transportation (WSDOT), Oregon Department of Transportation (ODOT), and California Department of Transportation (Caltrans). A method for classifying road damage from the 2020 wildfires is also presented, with classes labeled for traffic control, slope-rock scaling, hazard trees, and structures. Total anticipated costs incurred from the 2020 megafires for both temporary and permanent repairs included over US\begin{document}${\$} $\end{document}24 million for hazard trees, US\begin{document}${\$} $\end{document}17.5 million for slope-rock scaling, US\begin{document}${\$} $\end{document}43 million for structural damage, and over US\begin{document}${\$} $\end{document}3 million for traffic control. The total average cost of both temporary and permanent repairs per km of impacted route due to the 2020 Labor Day wildfires was about US\begin{document}${\$} $\end{document}127,783. These financial impacts can be used to better understand and manage risk attributable to this widespread and increasing hazard.